Fragmentation of International Law in the context of Institutional Crisis - Kaparov, A.S. (Право и государство, № 3 (108), 2025)
Recently, increasing fragmentation of international law – expressed in the growing number of special- ized norms, international organizations, and judicial bodies – has led to challenges in the global security system. This article offers a critical examination of fragmentation as a multidimensional phenomenon that encompasses normative, institutional, and procedural aspects of international legal regulation. The aim of the article is to reconsider fragmentation through the lens of institutional crisis and to explore its potential to create a flexible, multi-layered legal architecture at both global and regional levels. The author argues that while fragmentation may undermine the coherence of international law, it also offers a pragmatic framework for adapting legal systems in response to geopolitical instability and normative diversity. The study presents a structural analysis of fragmentation based on jurisprudence, treaty regimes, and doctrinal sources. The novelty lies in viewing fragmentation as a manifestation of legal pluralism – one that may function as a stabilizing force amid institutional decline and rising regionalism. Particular atten- tion is paid to the role of fragmentation in the formation of regional and specialized security instruments. It is argued that, under conditions of institutional crisis, fragmentation can serve as an effective model for conflict resolution and sustained legal cooperation
Keywords: international law, international courts, international relations, policy, fragmentation, regionalism, organizations, the United Nations, lex specialis, state